Kearifan Lokal dalam Pengelolaan Sumber Daya Hutan pada Masyarakat Seuneubok di Kecamatan Samadua Aceh Selatan - Ilyas Ilyas (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: People living in Seuneubok area and depending on forest to live have culturally got used to adopt with the forest ad its resoures. This culturally adjusted form or known wisdom is a traditional view concerning the relationship amng people internal and external community with their environment. This article aims at describing the perception of the people regarding this usage of the forest and the sustainability of the forest management and its resources function in their lebensraum, the standards or the norms as the guidance for the people in interacting with the forest resources located in the area of lebensraum in taking benefit and keeping its sustainability, to find out and explain what are the basic legality of the norms in terms of managing the resources in such place and the enforcement of the norms in the community. The Role of Local Wisdom in Managing Forest Resources in Seuneubok Sommunity in the Subdistrict of Samadua, South Aceh